Growth performance study of Silver barb (Barbonymus gonionotus) by replacing fishmeal with soybean meal in the diet (Asian Journal of Medical and Biological Research, 2020)
Increasing demand, uncertain availability, and increasing cost for fishmeal (FM), fish nutritionists have been driven to find alternative sources of protein. The aim of this study was to evaluate the effects of substituting FM with soybean meal (SM) on growth performance of silver barb, Barbonymus gonionotus. Five diets were prepared 0%SM (100%FM), 25%SM (75%FM), 50%SM (50%FM), 75%SM (25%FM) and 100%SM (0%FM) by replacing FM with SM. B. gonionotus having initial length and weight of 8.62±0.9 cm and 8.80±3.11 gm were fed each diet twice a day for 45 days. Fish sampling was done fortnightly. Significantly higher (P